2008
DOI: 10.2166/wst.2008.493
|View full text |Cite
|
Sign up to set email alerts
|

Use of microaerobic conditions for the improvement of anaerobic digestion of solid wastes

Abstract: The treatment of solid wastes containing slowly biodegradable compounds or high level of sulphur compounds was carried out. In both cases the application of microaerobic conditions (that means controlled dosing of small amount of air or oxygen into digester) was an efficient tool to increase the biodegradability of treated material and/or to increase the activity of methanogenic bacteria by removal of their inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 11 publications
(12 reference statements)
4
29
0
Order By: Relevance
“…In P7, the COD removal and methane yield declined simultaneously due to system reductive environment destruction ( Figure 2). As noted above, these results are consistent with those reported in literature, even on an industrial scale, it has been broadly demonstrated that the presence of limited amounts (not exceeding 15 mL in this study) of O2 in digesters does not negatively affect digestion performance [38,39].…”
Section: H 2 S and O 2 Concentration In Biogassupporting
confidence: 93%
“…In P7, the COD removal and methane yield declined simultaneously due to system reductive environment destruction ( Figure 2). As noted above, these results are consistent with those reported in literature, even on an industrial scale, it has been broadly demonstrated that the presence of limited amounts (not exceeding 15 mL in this study) of O2 in digesters does not negatively affect digestion performance [38,39].…”
Section: H 2 S and O 2 Concentration In Biogassupporting
confidence: 93%
“…The low current density led to limited oxygen formation, creating micro-aerobic conditions, which did not prevent methane production. Since the biomass granules in the UASB reactors are typically larger than 500 lm in diameter and the oxygen penetration depth does not exceed 50 lm( Quarmby and Forster, 1995;Thaveesri et al, 1995), the electrolytic oxygen might be consumed in the outer biofilm layer (Botheju et al, 2009;Jenicek et al, 2008;Jenicek et al, 2010;Kato et al, 1997;Shen and Guiot, 1996;Tan et al, 1999;Tartakovsky et al, 2006;Zhou et al, 2007).…”
Section: Comparing Ead and Ad Processesmentioning
confidence: 99%
“…at very low dissolved oxygen concentrations (Jagadabhi et al, 2010;Jenicek et al, 2008Jenicek et al, , 2010Shen and Guiot, 1996;Zitomer and Shrout, 1998). This improvement was attributed to the enhanced hydrolysis of complex organic matter (Botheju et al, 2009;Johansen and Bakke, 2006;Zhu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several biological methods have been studied for sulfide removal from the aqueous phase in anaerobic digesters, but in the last 8 years research on microaerobic anaerobic processes has increased significantly (van der Zee et al, 2007;Jenicek et al, 2008). This is based on the use of microorganisms capable of oxidizing hydrogen sulfide to elemental sulfur, which becomes the main process byproduct.…”
Section: Introductionmentioning
confidence: 99%